PENERAPAN METODE LOCATION BASED SERVICE (LBS) DALAM APLIKASI PRESENSI PEGAWAI PADA UNIVERSITAS DEHASEN BENGKULU - Haryanto, Muhammad Dicky Imansyah; Aspriyono, Hari; Suranti, Dewi (UNIB Press, 2024)
: This research develops a web-based attendance application using Location Based Service (LBS) technology at Dehasen University Bengkulu to overcome the limitations of fingerprint devices that often experience problems in recording fingerprints and other technical obstacles. The application was developed using the Waterfall method through the stages of needs analysis, system design, program code writing, testing, and implementation and maintenance. Designed using the Unified Modeling Language (UML) approach, and created using the Laravel framework and MySQL database. The attendance application has two main interfaces: admin and employee interface. The admin interface allows management of attendance data, real-time attendance monitoring, verification of leave or permission approval, and configuring attendance location points. The employee interface facilitates GPS-enabled attendance for inbound and outbound attendance, leave or permit applications, and access to attendance history. The test results show that the attendance application improves accuracy and efficiency in recording employee attendance. However, the presence application is still unable to detect location manipulation and further development is expected to detect or block location manipulation attempts.